2019
DOI: 10.1111/acel.12950
|View full text |Cite
|
Sign up to set email alerts
|

Targeting senescent cells alleviates obesity‐induced metabolic dysfunction

Abstract: Adipose tissue inflammation and dysfunction are associated with obesity‐related insulin resistance and diabetes, but mechanisms underlying this relationship are unclear. Although senescent cells accumulate in adipose tissue of obese humans and rodents, a direct pathogenic role for these cells in the development of diabetes remains to be demonstrated. Here, we show that reducing senescent cell burden in obese mice, either by activating drug‐inducible “suicide” genes driven by the p16Ink4a promoter or by treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
428
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 441 publications
(442 citation statements)
references
References 48 publications
14
428
0
Order By: Relevance
“…In addition to acquiring an oftentimes complex SASP, senescent cells can display a variety of biomarkers, including profound changes in heterochromatin (i.e., SADS) (27), DNA damage colocalized with telomeres (i.e., TAF) (28), and increased expression of the cyclin-dependent kinase inhibitors p16 Ink4a and p21 Cip1 (21). Accelerated accumulation of senescent cells has been identified in mice during obesity in adipose tissue, liver, and brain (13)(14)(15) and with T2D in the pancreas (e.g., senescent β cells) (16). In the latter study, HFD-induced obesity and insulin resistance in mice caused accelerated β cell senescence with a specific SASP, whereas senolysis (i.e., clearance of senescent cells) using either genetic or pharmacological approaches improved glucose homeostasis, β cell function, and the gene expression profile of β cells (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to acquiring an oftentimes complex SASP, senescent cells can display a variety of biomarkers, including profound changes in heterochromatin (i.e., SADS) (27), DNA damage colocalized with telomeres (i.e., TAF) (28), and increased expression of the cyclin-dependent kinase inhibitors p16 Ink4a and p21 Cip1 (21). Accelerated accumulation of senescent cells has been identified in mice during obesity in adipose tissue, liver, and brain (13)(14)(15) and with T2D in the pancreas (e.g., senescent β cells) (16). In the latter study, HFD-induced obesity and insulin resistance in mice caused accelerated β cell senescence with a specific SASP, whereas senolysis (i.e., clearance of senescent cells) using either genetic or pharmacological approaches improved glucose homeostasis, β cell function, and the gene expression profile of β cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified senescent cells in the bone microenvironment with aging (11) and found that targeting cellular senescence improved age-related bone loss (12). Furthermore, senescence has been shown to increase in adipose tissue, liver, and brain during obesity (13)(14)(15) and in pancreatic β cells, contributing to T2D (16). This led us to hypothesize that cellular senescence may be a mechanistic link between poor bone quality and T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mRNA expression of senescence marker genes, P53, P21 and P16 were increased in the senescent AML12 cells compared to control AML12 cells (Figure 1d). Similarly, the expression of these genes also was increased in livers from old mice (100-108 week age) compared to those from young mice (12)(13)(14)(15)(16)(17)(18)(19)(20) week age) (Figure 1e). Furthermore, multiple H2O2 treatments increased senescence since there was increased activated -Gal (SA -Gal)-positive cells (Figure 2a,b) and H2A.X-positive cells containing condensed chromatin in larger nuclei (Figure 2c,d).…”
Section: Senescence Induction and Validation In Aml12 Cellsmentioning
confidence: 82%
“…Recent studies in the liver show that inducing hepatocyte senescence promotes fat accumulation and hepatic steatosis in vitro and in vivo [17]. Likewise, targeting senescent hepatocytes and adipocytes reduce overall hepatic steatosis and improve obesity-induced metabolic dysfunction [14,17]. These findings suggest that senescence plays an important role in the development of chronic hepatic diseases and their metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation